Social Relationships between Teachers and Learners, Learners' Mathematical Identities and Equity. Issue 2 (4th May 2019) - Gardee, Aarifah
Abstract : In recent years, the notion of equity has become increasingly prominent in mathematics education, in relation to pedagogy and the opportunities provided for learners to identify themselves as successful mathematics learners. Different pedagogies have been shown to promote equity and access to mathematics in different ways. However, teacher practices are not characterised only by pedagogy, but also by social relationships between teachers and learners, which can be key in supporting all learners to identify with mathematics. Data are drawn from a study involving two teachers who taught using similar traditional pedagogies but had different social relationships with learners in a South African school. Data were collected over two years, in the form of videotaped lessons, field notes and audiotaped interviews with participants, and were analysed qualitatively. The relationship between different teacher–learner social relationships and learners' mathematical identities suggests that different social relationships have implications for equity, shaping access to knowledge and learner identities in important ways.